Pengaruh Gaya Kepemimpinan Transformasional dan Motivasi Kerja Pada Perilaku Etis Manajer Koperasi - Candra Kusuma Dewi, Ni Kadek; Widanaputra, A.A. Gde Putu (E-Jurnal Akuntansi, 2020)
The ethical behavior of managers greatly influences the success of an organization. But in practice, not a few managers who work outside the rules that have been set so that it behaves unethically. This research was conducted to obtain empirical evidence regarding the influence of transformational leadership styles and work motivation on the ethical behavior of cooperative managers. This research was conducted in 48 cooperatives in Tabanan Regency. Based on the results of this study indicate that the transformational leadership style has a significant insignificant positive effect on the ethical behavior of cooperative managers, which means that transformational leadership styles are not able to influence the ethical behavior of cooperative managers. Work motivation has a significant positive effect on the ethical behavior of cooperative managers, which means that the higher the work motivation of managers, the higher the ethical behavior of cooperative managers. Keywords: Transformational Leadership Style; Work Motivation; Manager Ethical Behavior.